2010
DOI: 10.1080/00986445.2010.499841
|View full text |Cite
|
Sign up to set email alerts
|

Highly Concentrated Emulsions: Role of Droplet Size

Abstract: The problem of droplet size dependence on rheological properties of highly concentrated emulsions was studied. Changes in droplet size distribution were achieved by multi-pass flow through a small orifice set as the outlet of a piston-chamber pumping instrument, and extended elongation of droplets combined with the transienttransition flow regime (laminar=turbulent) at the outlet of the orifice provided the shift of the droplet sizes to the smaller-size side of the distribution. Their distributions were wider … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 34 publications
(37 reference statements)
1
7
0
Order By: Relevance
“…The viscosity of the HIPEs increased significantly when the dosage of SDS was increased from 0.8 to 1.0 wt %. This finding is in agreement with the reported results that the reduction in droplet average diameter would significantly improve the properties of the emulsions, such as the viscosity, yield stress, and storage modulus, which is caused by the thinner intervening liquid layers between the droplets result in tighter packing of droplets and higher effective viscosity. When the dosage of SDS used was above 1.0 wt %, the viscosity of the HIPEs decreased, even though the droplet size decreased. The possible reason for this observation is that SDS contributed more on stabilizing the emulsions at high SDS dosage, a part of EHL was liberated and played the role of dispersant, which results in lower viscosity.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The viscosity of the HIPEs increased significantly when the dosage of SDS was increased from 0.8 to 1.0 wt %. This finding is in agreement with the reported results that the reduction in droplet average diameter would significantly improve the properties of the emulsions, such as the viscosity, yield stress, and storage modulus, which is caused by the thinner intervening liquid layers between the droplets result in tighter packing of droplets and higher effective viscosity. When the dosage of SDS used was above 1.0 wt %, the viscosity of the HIPEs decreased, even though the droplet size decreased. The possible reason for this observation is that SDS contributed more on stabilizing the emulsions at high SDS dosage, a part of EHL was liberated and played the role of dispersant, which results in lower viscosity.…”
Section: Resultssupporting
confidence: 91%
“…The 5.0 wt % EHL and 1.0 wt % SDS costabilized HIPEs have the largest yield stress when the oil content is 80 vol %. This further demonstrates that smaller droplet size and tighter overall droplet packing resulted in a thicker emulsion, which is more resistant to the deformation and also beneficial for the stability of HIPEs. Both |η*| and tan δ are important parameters for the storage stability of dispersions. Larger |η*| values and lower tan δ values present better stability and elastic behavior for emulsions in the linear viscoelastic region .…”
Section: Resultsmentioning
confidence: 90%
“…HCEs are characterized as viscoplastic liquids with complex flow behavior. A number of studies were reported on the influence of various governing factors on the rheological characteristics of HCEs, and emulsion explosives in particular. …”
Section: Introductionmentioning
confidence: 99%
“…For HIPEs with a defined composition and internal/external phase volume fraction, the decrease in MDD greatly altered the rheological properties of the emulsion. 56 This was evidenced by the dramatic increase in the viscosity, σ c , and G′ values. At higher PGPR concentrations, the droplets showed smaller MDD, which improved the shear resistance of the emulsions.…”
Section: Microstructures Of W/o Hipesmentioning
confidence: 96%